Prologue to the work Knowledge about the Nitra Chair by Matej Bel - Župčán, Ladislav (Études sur la Région Méditerranéenne, 2021)
Polyhistor Matej Bel (1684–1749) is one of the leading scholars working in the Hungarian environment. His top multi-volume work entitled Notitia hungariae novae historicogeographica. The gradual elaboration of patriotic-geographical works containing a number of key facts from individual stools belonging to the Habsburg Monarchy was started. The presented study is an introduction to the passage of the Nitra seat based on the existing manuscripts of Matej Bel, but also his assistants (former students and collaborators) who participated in the design of the final form of the written volume. A key element of the paper is the basic characteristics of the source documents, which directly related to the Nitra capital, as well as the list of contributors. Individual manuscripts were identified by archival work abroad (Hungarian National Library and Hungarian Landscape Archive).